Relevance of ASEAN in a shifting global environment - Hussain, Nazia (2024)
Increasing strategic competition among major powers poses a challenge to ASEAN unity and ASEAN Centrality. ASEAN must refurbish and strengthen its existing mechanisms as it strives to maintain the organisation’s relevance in multilateralism and the rules-based international order, and to consolidate the growth, prosperity, and security of individual member states.